The Demand for Good Government - Davis, Michael L.; Hayes, Kathy (The Review of Economics and Statistics, 1993)
The efficiency of governments may be influenced by institutional factors and by the intensity of monitoring by citizens. This paper develops a theory of optimal monitoring and then uses frontier estimation techniques to construct measures of efficiency f or police departments in 141 cities. Using these efficiency measures, i t is possible to test the extent to which efficiency is influenced by the presence of a professional city manager and by characteristics of th e citizens. Copyright 1993 by MIT Press.